Classified Plant Al-Dhahiriya in the South of Palestine (Indian Journal of Advanced Botany (IJAB), 2024)
We studied plant species of Dhahiriya in the period between January to October 2021, and January to Jun 2024, due to the importance of plants in that vital part of Palestine, which is located in southern Palestine, including that region’s climate, and unique plants that represent of the Mediterranean region plants, North Africa, Sinai desert, Negev, Dead Sea, and Red Sea. It used the Braun-Blanquet (1979) method for the identification of plants. Moreover, Plants have been studied in Dhahiriya, located in southern Palestine. A total of 770 species from 70 families were identified, of which 86 (11.16%) are endemic. The plant families with the highest representation were Asteraceae (14.54%), Fabaceae (14%), Poaceae (7.41%), and Lamiaceae (5.19%). Regarding plant life forms, Therophytes account for 47%, Hemicryptophytes for 20.35%, Shrubs or Chamaephytes for 14.05%, and Trees or Phanerophytes for 9.05%, with a notable increase in spring.